HIV and Liver Disease - Sherman, Kenneth E.; Sherman, Kenneth E. (Springer New York : Imprint: Springer, 2012)
Liver disease has been identified as a leading cause of death in HIV-infected patients since the introduction of highly active antiretroviral therapy (HAART) in 1996. The HIV treatment community has been caught largely unaware of this emerging dilemma. Many HIV care providers are ill-equipped to understand and interpret liver injury patterns, or to provide comprehensive care and management for viral coinfections which they are not familiar with. HIV and Liver Disease provides a comprehensive update of the field covering the epidemiology, pathogenesis, management and treatment of liver disease in patients with HIV infection. The volume will help HIV care providers understand and interpret liver injury patterns, and/or provide comprehensive care and management for viral coinfections. Gastroenterologists and hepatologists will gain an understanding of complex drug regimens that are used to treat HIV and which may impact HCV and HBV treatment. Written by expert clinicians and researchers across multiple disciplines, HIV and Liver Disease will be of great value to gastroenterologists, hepatologists, infectious disease practitioners, as well as other health care providers who provide care or participate in research in the field of HIV.